Biorefinery co-products phytochemicals, primary metabolites and value-added biomass processing - Bergeron., Chantal, 1967-; Carrier, Danielle Julie, 1959-; Ramaswamy, Shri, 1957-; Books24x7, Inc. (Chichester, West Sussex, U.K. : John Wiley & Sons, 2012)
"In order to successfully compete as a sustainable energy source, the value of biomass must be maximized through the production of valuable co-products in the biorefinery. Specialty chemicals and other biobased products can be extracted from biomass prior to or after the conversion process, thus increasing the overall profitability and sustainability of the biorefinery. Biorefinery Co-Products highlights various co-products that are present in biomass prior to and after processing, describes strategies for their extraction, and presents examples of bioenergy feedstocks that contain high value products. Topics covered include: Bioactive compounds from woody biomass; Phytochemicals from sugar cane, citrus waste and algae; Valuable products from corn and other oil seed crops; Proteins from forages; Enhancing the value of existing biomass processing streams. Aimed at academic researchers, professionals and specialists in the bioenergy industry, Biorefinery Co-Products is an essential text for all scientists and engineers working on the efficient separation, purification and manufacture of value-added biorefinery co-products."--Unedited summary from book.
Title from title screen.
.
Includes bibliographical references and index.
Text.
Available also in a print ed.
Mode of access: Internet via World Wide Web.
Keywords: Biomass -- Processing -- By-products.; Agricultural processing; Biomass energy; Renewable energy sources; Electronic books; Electronic books